Data: Superior Rate Capability of High Mass Loading Supercapacitors Fabricated with Carbon Recovered from Methane Cracking - Kahagala Gamage, Upul (Cranfield University, 2023)
This folder contains all data files related to the publication "Superior Rate Capability of High Mass Loading Supercapacitors Fabricated with Carbon Recovered from Methane Cracking"
Keywords: 'supercapacitors'; 'carbon nanotubes'; 'porous nanocarbon-based electrodes'; 'methane cracking'; 'rate capability'; 'electrochemistry'; 'electrochemical impedance spectroscopy'